2016
DOI: 10.1002/jcla.22051
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study Between Point‐of‐Care Testing Systems and Central Laboratory for Determining Blood Glucose in Venous Blood

Abstract: The POCT system cannot replace the central laboratory system as a provider of a standard result in clinical diagnosis. It can only be used as a screening test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
10
2
Order By: Relevance
“…These findings are different from previous recent studies that showed similar measurements for the two methods [10,11,14,22]. These findings are different from previous recent studies that showed similar measurements for the two methods [10,11,14,22].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These findings are different from previous recent studies that showed similar measurements for the two methods [10,11,14,22]. These findings are different from previous recent studies that showed similar measurements for the two methods [10,11,14,22].…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast, previous studies reported decreased accuracy with very high glucose concentration (≥ 5.6 mmol/l) [11,[24][25][26]. hypoglycaemic) ranges or for low glucose concentration (<5.6 mmol/l).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations